Detecting jumps in correlated series - Islam, M Shahidul (Bangladesh Journal of Scientific Research, 2012)
No abstract available DOI: http://dx.doi.org/10.3329/bjsr.v25i1.13053 Bangladesh J. Sci. Res. 25(1): 87-91, 2012